2015
DOI: 10.1038/nn.4068
|View full text |Cite
|
Sign up to set email alerts
|

Coding the direct/indirect pathways by D1 and D2 receptors is not valid for accumbens projections

Abstract: Summary It is widely accepted that D1 dopamine receptor-expressing striatal neurons convey their information directly to the output nuclei of the basal ganglia while D2-expressing neurons do so indirectly via pallidal neurons. Combining optogenetics and electrophysiology we show that this architecture does not apply to mouse nucleus accumbens projections to the ventral pallidum. Thus, current thinking attributing D1/D2 selectivity to accumbens projections akin to dorsal striatal pathways needs to be reconsider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
356
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(382 citation statements)
references
References 25 publications
23
356
3
Order By: Relevance
“…In a recent study (Kupchik et al, 2015), we provided the first definitive evidence that the direct and indirect pathways of the NAc are not coded by MSN cell types (Figure 1). Using optogenetics in transgenic mice combined with neural tracing tools we showed that D1-MSNs comprise a significant portion of the classical indirect pathway by synapsing on VP neurons that project to the VM.…”
Section: Funding and Disclosurementioning
confidence: 69%
“…In a recent study (Kupchik et al, 2015), we provided the first definitive evidence that the direct and indirect pathways of the NAc are not coded by MSN cell types (Figure 1). Using optogenetics in transgenic mice combined with neural tracing tools we showed that D1-MSNs comprise a significant portion of the classical indirect pathway by synapsing on VP neurons that project to the VM.…”
Section: Funding and Disclosurementioning
confidence: 69%
“…S1 B and C). Anatomically, D1-MSNs and D2-MSNs in dorsal striatum project to distinct brain areas (22) but projections of D1-MSNs and D2-MSNs from the NAc are more overlapping and remain to be further defined (11,23). Importantly, stimulation of MSNs by dopamine results in opposite regulation of cAMP and PKA via stimulatory G protein (G s /G olf )-mediated signaling in D1-MSNs compared with inhibitory G protein (G i /G o )-mediated signaling in D2-MSNs (24).…”
Section: Resultsmentioning
confidence: 99%
“…Although the literature has been consistent in this regard, an important caveat that is discussed in more detail in this section is that although behaviors coded by D1 and D2 MSNs are traditionally interpreted as mediated by the direct and indirect pathways, respectively, D1 and D2 accumbens MSNs send a mixed projection to the VP, making the classic interpretation of direct and indirect pathways at least partly incorrect (Kupchik et al, 2015).…”
Section: A Medium Spiny Neuronsmentioning
confidence: 99%
“…Nucleus Accumbens Core Efferents. The NAcore sends projections primarily to GABAergic basal ganglia nuclei, but it also contains neurons that send inputs directly to glutamatergic neurons in the subthalamus and dopaminergic neurons in the paranigral part of the VTA (Groenewegen et al, 1999;Tripathi et al, 2010;Watabe-Uchida et al, 2012;Bocklisch et al, 2013;Matsui et al, 2014;Kupchik et al, 2015). The NAcore also projects to the substantia nigra pars reticulata and sends a striatopallidal projection to the dorsolateral VP and lateral globus pallidus (Heimer et al, 1991;Tripathi et al, 2010).…”
Section: A Nucleus Accumbens Corementioning
confidence: 99%
See 1 more Smart Citation